Macroeconomic impacts of Canadian immigration: Results from a macro-model - Peter Dungan; Tony Fang; Morley Gunderson (Institute for the Study of Labor (IZA), 2012)
We use a macro-econometric forecasting model to simulate the impact on the Canadian economy of a hypothetical increase in immigration. Our simulations generally yield positive impacts on such factors as real GDP and GDP per capita, aggregate demand, investment, productivity, and government expenditures, taxes and especially net government balances, with essentially no impact on unemployment. This is generally buttressed by conclusions reached in the existing literature. Our analysis suggests that concern should be with respect to immigrants themselves as they are having an increasingly difficult time assimilating into the Canadian labour market, and new immigrants are increasingly falling into poverty.
Keywords: J15; E17; J18; 330; macroeconomic impact; immigration; FOCUS Model; Canada; Einwanderung; Makroökonomischer Einfluss; Simulation; Kanada